Penny Postcard Image of Fifth Street, Downtown Oxnard, CA - United States Post Office::::::
Penny postcard image of Fifth Street in downtown Oxnard, CA ca. 1900. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.